PRRT2 gene mutations associated with infantile convulsions induced by sucking and the genotype-phenotype correlation - Liu, De-Tian; Tang, Xue-Qing; Wan, Rui-Ping; Luo, Sheng; Guan, Bao-Zhu; Li, Bin; Liu, Li-Hong; Li, Bing-Mei; Liu, Zhi-Gang; Xie, Long-Shan; Yi, Yong-Hong (Frontiers in Neurology, 2022)
Introduction: PRRT2 is a major causative gene for self-limited familial neonatal-infantile epilepsy, paroxysmal kinesigenic dyskinesia, and paroxysmal kinesigenic dyskinesia with infantile convulsions. Voluntary movement trigger is prominent in adolescence and adulthood, but the triggers are unknown in infants. Methods: A gene panel designed for targeted next-generation sequencing was used to screen genetic abnormalities in a cohort of 45 cases with infantile convulsions. The copy number variation was detected by a computational method based on the normalized depth of coverage and validated by quantitative real time-polymerase chain reaction method. The genotype-phenotype correlation of the PRRT2 mutation gene was analyzed. Results: A de novo heterozygous PRRT2 deletion was identified in a child who had infantile convulsions induced by vigorous sucking. Seizures happened during the change of feeding behavior from breast to formula, which led to hungry and vigorous sucking. Ictal electroencephalograms recorded seizures with focal origination, which provided direct evidence of epileptic seizures in infants with PRRT2 mutations. Seizures stopped soon after the feeding behavior was changed by reducing feeding interval time and extending feeding duration. Data re-analysis on our previously reported cases with PRRT2 mutations showed that six of eighteen (33.3%) patients had infantile convulsions or infantile non-convulsion seizures during feeding. The mutations included two truncating mutations (c.579dupA/p.Glu194Argfs*6, and c.649dupC/p.Arg217Profs*8) that were identified in three affected individuals each. Conclusions: This study suggests that feeding, especially vigorous sucking is potentially a trigger and highlights the significance of feeding behavior in preventing seizures in infants with PRRT2 mutations. Identification of PRRT2 haploinsufficiency mutations in the patients with infantile convulsions induced by sucking suggested a potential genotype-phenotype correlation.